Biallelic Mutations in SLC1A2; an Additional Mode of Inheritance for SLC1A2-Related Epilepsy - Wagner, Matias; Gusic, Mirjana; Günthner, Roman; Alhaddad, Bader; Kovacs-Nagy, Reka; Makowski, Christine; Baumeister, Friedrich; Strom, Tim; Meitinger, Thomas; Prokisch, Holger; Wortmann, Saskia B. (Neuropediatrics, 2018)
Recently, heterozygous de novo mutations in SCL1A2 have been reported to underlie severe early-onset epileptic encephalopathy. In one male presenting with epileptic seizures and visual impairment, we identified a novel homozygous splicing variant in SCL1A2 (c.1421 + 1G > C) by using exome sequencing. Functional studies on cDNA level confirmed a consecutive loss of function. Our findings suggest that not only de novo mutations but also biallelic variants in SLC1A2 can cause epilepsy and that there is an additional autosomal recessive mode of inheritance. These findings also contribute to the understanding of the genetic mechanism of autosomal dominant SLC1A2-related epileptic encephalopathy as they exclude haploinsufficiency as exclusive genetic mechanism.
Keywords: epilepsy; seizure; visual impairment; SLC1A2; exome sequencing